Reagentless Bacterial Identification Using a Combination of Multiwavelength Transmission and Angular Scattering Spectroscopy. (29th February 2016) - Huffman, Debra E.; Serebrennikova, Yulia M.; Smith, Jennifer M.; Roth, Alison; Lindon, Jack N.; Leparc, German F.; Garcia-Rubio, Luis H.
Abstract : Optics based technologies are being advanced by many diagnostic companies around the globe. This resurgence is being driven by several factors including novel materials, enhanced computer power, nonlinear optics, and advances in algorithmic and statistical analysis. This study expands on a previous paper that evaluated the capability of a reagent-free optical profiling platform technology that used multiwavelength transmission spectroscopy to identify bacterial pathogens from pure culture. This study combines multiwavelength angular scattering with transmission based analysis into a single algorithm that will identify bacterial pathogens. Six predominant organisms, S. aureus, E. coli, K. pneumoniae and P. aeruginosa, E. faecalis, and coagulase negative Staphylococcus, were analyzed from a total of 753 clinical isolates received from three large community hospital systems. The bacterial identification method used for comparison in this study was the Vitek-2 (bioMerieux) which utilizes a biochemically based identification system. All of the clinical isolates received were blinded as to their identification until completion of the optical analysis. Sensitivities ranged from 87.7 to 94.6% with specificities ranging from 97.2 to 99.9% indicating that optical profiling is a powerful and exciting new technology that could be developed for the rapid identification of pathogens without the use of chemical reagents.